A comparative analysis of road and vehicle qualities as factors of road traffic carnage in Nigeria - Onyenekenwa Cyprian Eneh; Andy Okosun; Idu R Egbenta; Nicholas I Obi; Martin C Oloto; Obinna Ubani; Chinemelum A Eneh; Cosmas I Eneonwo (BMC, 2023)
Abstract Background and objective Carnage on roads is a growing concern in Nigeria. Over 27 persons, equivalent to more than 4 families, die daily from road traffic crashes. Two direct factors of a road crash are road quality and vehicle quality. To interrogate and compare both factors to road traffic accidents, the longitudinal study regressed secondary data on death tolls against road quality and vehicle quality. Materials and methods Data on the estimated number of vehicles imported into Nigeria (1992-2021) served as the indicator of vehicle quality on Nigerian roads. The longitudinal study regressed secondary data on death tolls (2013-2019) against road quality (2006-2019) and vehicle quality (1992-2021). Results Results showed that road quality is degenerating as well as vehicle quality in Nigeria, resulting in increase in the number of road traffic crashes and the attendant death tolls. For every 1% decrease in road quality, death tolls from road traffic crashes in Nigeria increased by 0.00642% at 5% significance, and for every decrease in vehicle quality, death tolls from road traffic crashes in Nigeria increased by 0.327% at 5% significance. Conclusion The study recommended increased advocacy on the sanctity of life and the need for all tiers of government to prioritize policy and implementation of improving the road quality and vehicle quality to reduce road traffic crashes and save lives on Nigerian roads.